Formation of beach‐ridge plains: an appreciation of the contribution by Jack L. Davies. (10th August 2016) - Oliver, Thomas S.N.; Thom, Bruce G.; Woodroffe, Colin D.
Abstract: A robust debate among coastal geomorphologists as to the processes by which beach‐ridge plains around Australia have formed was initiated by a former President of the Institute of Australian Geographers. This review gives special consideration to the work of Jack L. Davies, whose academic contributions to coastal geomorphology in Australia have not always been appropriately acknowledged when explaining how similar plains have evolved elsewhere in the world. Davies recognised that relatively steep storm waves caused erosion (cut) on beaches, whereas less steep long‐period swell waves returned sand (fill). He considered the beach berm to be the nucleus on which a beach ridge formed, which could subsequently develop into a foredune, in contrast to cobble ridges that were deposited during storms. Offshore conditions regulate supply of sand to the shoreline, partly through effects on wave refraction, with higher rates of supply where the nearshore is shallow. It was apparent to Davies that the elevation of successive ridges might, but not necessarily, provide evidence of past changes of sea level, despite adornment by variable amounts of windblown dune sand. Morphodynamic understanding of long‐term coastal evolution, based on radiocarbon dating chronologies, has demonstrated that Australian coastal plains formed over the past 6, 000 years when sea level has been close to its present level, in contrast to several documented locations in the northern hemisphere where the sea has been rising for the past few millennia. Particularly insightful were observations by Davies that ridge formation could be influenced by a range of factors including changes in sea level, storminess, or sediment supply. These factors acting singly or in combination seem likely to change in the future. Understanding such responses remains a high priority and can be addressed by new technologies, such as light detection and ranging, optically stimulated luminescence dating, ground‐penetrating radar, and computer simulation.